Exploring the Old Testament - Schultz, Samuel J.; Smith, Gary V., 1943- (Wheaton, IL Crossway, 2001)
Includes bibliographical references.
Originally published: Old Testament survey. Wheaton, IL. : Evangelical Training Association, 1964.
Keywords: Bible. O.T. -- introductions